Delayed urologic cancer care in the COVID‐19 pandemic: Patients' experiences. (9th August 2022) - Glick, Hannah; Sarin, Aashima; Herrel, Lindsey A.; Ma, Lindsay; Moore, Marissa; Van Wieren, Inga; Chisolm, Stephanie; O'Dell, Diana; Duby, Ashley; Morgan, Todd M.; Montie, James E.; Wittmann, Daniela
Abstract: Objective: To understand experiences of patients with genitourinary cancer who experienced delayed cancer care due to the COVID‐19 pandemic. Methods: We conducted a mixed methods study with an explanatory sequential design. Qualitative findings are reported here. Patients with muscle invasive bladder, advanced prostate or kidney cancer were eligible. Participants were selected for interviews if they self‐reported low (0–3/10) or high (6–10/10) levels of distress on a previous survey. Participants were interviewed about their experiences. Interviews were transcribed, coded and categorised using thematic data analysis methodology. Results: Eighteen patients were interviewed. Seven had prostate cancer, six bladder cancer and five kidney cancer. Six themes were derived from the interviews: (1) arriving at cancer diagnosis was hard enough, (2) response to treatment delay, (3) labelling cancer surgery as elective, (4) fear of COVID‐19 infection, (5) quality of patient‐provider relationship and communication and (6) what could have been done differently. Conclusion: These findings offer insight into the concerns of patients with genitourinary cancers who experienced treatment delays due to COVID‐19. This information can be applied to support patients with cancers more broadly, should treatment delays occur in the future.